Nonwoven fabric laminate

The nonwoven laminate with a two-layer substrate and inorganic particle layers on both sides addresses the challenges of heat resistance and fiber peeling, achieving dimensional stability and performance suitable for building and industrial applications.

JP2025039248APending Publication Date: 2025-03-21MITSUBISHI PAPER MILLS LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023146198
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing nonwoven laminates using inorganic fibers face challenges in combining high heat resistance with dimensional stability and preventing the scattering and peeling of inorganic fibers, which affects their performance in building and industrial applications.

Method used

A nonwoven laminate with a two-layer substrate structure, comprising a surface nonwoven fabric layer with inorganic fibers, wet and heat-adhesive binder fibers, and fibrillated fibers, and a back nonwoven fabric layer with heat-fused binder fibers, is developed. This laminate includes inorganic particle layers on both sides of the substrate to enhance heat resistance and prevent fiber peeling.

Benefits of technology

The proposed nonwoven laminate achieves dimensional stability, high heat resistance, and effective prevention of inorganic fiber peeling, making it suitable for demanding applications in building and industrial materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039248000001
    Figure 2025039248000001
  • Figure 2025039248000002
    Figure 2025039248000002
Patent Text Reader

Abstract

To provide a nonwoven fabric laminate which can be used as a building material or an industrial member and has high heat resistance and has the ability to prevent inorganic fibers from falling off.SOLUTION: The problem is solved by a nonwoven fabric laminate which has a base material and inorganic particle layers on both sides of the base material, wherein the base material has a two-layer structure of a nonwoven fabric layer containing inorganic fibers, wet-heat-adhesive binder fibers, and fibrillated fibers and a nonwoven fabric layer containing heat-adhesive binder fibers, the content of the inorganic fibers in the base material is 70 mass% or more and less than 95 mass% relative to the base material, and the inorganic particle layer contains inorganic particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-resistant nonwoven fabric laminate suitable for use as a building material or industrial member. [Background technology]

[0002] Inorganic fibers, especially glass fibers, are inexpensive and have excellent heat resistance and flame retardancy, and therefore have been widely used in building materials, automobile parts, insulators, industrial parts, and the like. In building materials, inorganic fibers are used for applications requiring flame retardancy, heat resistance, and non-combustibility, such as wallpaper materials, cushion flooring, and ceiling materials. In automobile parts, inorganic fibers are used for applications such as battery covers, brake pads, front bumpers, ceiling materials, and interior materials. In addition, several applications of nonwoven fabrics using inorganic fibers such as glass fibers have been proposed. However, inorganic fibers such as glass fibers contained in nonwoven fabrics have the characteristic of easily falling off and scattering, which may result in contamination of subsequent processing steps with inorganic fibers. In addition, inorganic fibers such as glass fibers are irritating to human skin, and therefore scattered inorganic fibers may adhere to workers and cause inflammation, etc. If a large amount of binder or pulp is blended into the nonwoven fabric to suppress scattering of inorganic fibers, the flame retardancy, heat resistance, and non-combustibility expected for fire prevention and use in the engine room of an automobile, etc., cannot be satisfied. For this reason, it is extremely difficult to obtain a nonwoven fabric that has both the ability to inhibit the inorganic fibers from falling off and high heat resistance.

[0003] As an intermediate base material for building materials, a wet-laid nonwoven fabric composed of two layers, a layer containing inorganic fibers and moist heat-adhesive binder fibers and a layer containing heat-fusible binder fibers, is known (see, for example, Patent Document 1). The wet-laid nonwoven fabric described in Patent Document 1 has a surface layer containing inorganic fibers and moist heat-adhesive binder fibers and a back layer containing heat-fusible binder fibers, the surface layer being for uniformly penetrating resin, and the back layer being for reducing irritation to the human body. The wet-laid nonwoven fabric described in Patent Document 1 has high breathability, is easily permeable to coating liquids such as polyvinyl chloride for obtaining quality for building materials, has dimensional stability when processed into building materials, is less likely to generate fluff, has excellent surface quality, and has strength suitable for processing. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-086477 A Summary of the Invention [Problem to be solved by the invention]

[0005] One of the problems to be solved by the wetlaid nonwoven fabric described in Patent Document 1 is the "permeability of coating liquid" of polyvinyl chloride, etc. Therefore, the wetlaid nonwoven fabric described in Patent Document 1 does not essentially have the technical idea of ​​providing an inorganic particle layer on the wetlaid nonwoven fabric. An object of the present invention is to provide a nonwoven fabric laminate which has conventional dimensional stability and low fuzzing properties, while also suppressing shedding of inorganic fibers and providing high heat resistance. [Means for solving the problem]

[0006] As a result of intensive research to solve the above problems, the following invention was discovered.

[0007] [1] A nonwoven fabric laminate comprising a substrate and inorganic particle layers on both sides of the substrate, the substrate having a two-layer structure comprising a nonwoven fabric layer containing inorganic fibers, heat-adhesive binder fibers under moisture, and fibrillated fibers, and a nonwoven fabric layer containing heat-fusible binder fibers, the content of the inorganic fibers in the substrate being 70% by mass or more and less than 95% by mass with respect to the substrate, and the inorganic particle layer containing inorganic particles.

[0008] [2] The nonwoven fabric laminate according to [1] above, wherein the inorganic particle layer contains a binder.

[0009] In this specification, the "content" is a value (% by mass) calculated from the amount of dry solids (mass of dry solids) for each target area of ​​each target object. Effect of the Invention

[0010] The nonwoven fabric laminate of the present invention has the conventional dimensional stability and resistance to fluffing, while also being able to suppress shedding of inorganic fibers and having high heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The nonwoven fabric laminate has a substrate and inorganic particle layers on both sides of the substrate. The substrate has a two-layer structure consisting of a nonwoven fabric layer containing inorganic fibers, moist heat adhesive binder fibers, and fibrillated fibers, and a nonwoven fabric layer containing heat-fusible binder fibers. The inorganic particle layer contains inorganic particles. The nonwoven fabric layer containing inorganic fibers, moist heat adhesive binder fibers, and fibrillated fibers is hereinafter referred to as the "surface nonwoven fabric layer" for convenience. The nonwoven fabric layer containing heat-fusible binder fibers is hereinafter referred to as the "backside nonwoven fabric layer" for convenience.

[0012] The substrate of the nonwoven fabric laminate has a two-layer structure consisting of a surface nonwoven fabric layer and a back nonwoven fabric layer. This two-layer structure allows the nonwoven fabric laminate to obtain the conventional dimensional stability and reduced fuzz generation, as described in Patent Document 1. The surface nonwoven fabric layer containing inorganic fibers, heat-adhesive binder fibers under moist conditions, and fibrillated fibers can suppress the shedding of the inorganic fibers by blending the fibrillated fibers and entangling the fine fibrillated fibers with the rigid inorganic fibers. In addition, since the inorganic particle layers are provided on both sides of the substrate, the inorganic particle layers can protect the moist heat adhesive binder fibers, fibrillated fibers, and heat fusible binder fibers, which have poor heat resistance. As a result, the nonwoven fabric laminate has good heat resistance. In addition, since the inorganic particle layers are provided on both sides of the substrate, even if the inorganic fibers fall off the substrate, they are less likely to be released to the outside of the nonwoven fabric laminate. As a result, the nonwoven fabric laminate can suppress the fall-off of the inorganic fibers.

[0013] In some embodiments, the ratio of the content of the front nonwoven fabric layer to the back nonwoven fabric layer in the substrate is in the range of 70:30 to 99:1 (front nonwoven fabric layer:back nonwoven fabric layer). This is because the heat resistance of the nonwoven fabric laminate is improved. In addition, this is because the substrate has excellent handleability during processing and application when used as a building material or industrial member.

[0014] The inorganic fibers are conventionally known in the field of nonwoven fabrics. Examples of the inorganic fibers include ceramic fibers such as silica fibers, alumina fibers, alumina silicate fibers, zirconia fibers, carbon fibers, soluble fibers, refractory ceramic fibers, aerogel composite fibers, magnesium silicate fibers, alkaline earth silicate fibers, potassium titanate fibers, and potassium titanate whisker fibers, glass fibers such as glass fibers, chopped strands, and glass wool, and mineral fibers such as rock wool, basalt fibers, and wollastonite fibers. In some embodiments, the inorganic fibers are one or more selected from the group consisting of these. In some embodiments, the inorganic fibers include glass-based fibers such as glass fibers, chopped strands, and glass wool. In at least one embodiment, the inorganic fibers include glass fibers because they are excellent for forming a nonwoven layer. That is, in at least one embodiment, the nonwoven fabric laminate has a substrate and inorganic particle layers on both sides of the substrate, the substrate has a two-layer structure consisting of a front nonwoven fabric layer and a back nonwoven fabric layer, the inorganic fibers contain glass fibers, and the inorganic particle layers contain inorganic particles.

[0015] In some embodiments, the average fiber diameter of the inorganic fibers is 1 μm or more and 11 μm or less. This is because, when the average fiber diameter of the inorganic fibers is in the above range, the strength of the surface nonwoven fabric layer and the formation of appropriate gaps in the surface nonwoven fabric layer can be well achieved. As a result, when an inorganic particle layer described later is provided on the surface nonwoven fabric layer, the formation of the inorganic particle layer is stabilized.

[0016] The cross-sectional shape of the inorganic fibers may be any of a circular shape, an elliptical shape, a flat shape, etc. When the cross-sectional shape of the inorganic fibers is a flat shape, the dimensions of the average major axis and the average minor axis of the flat shape are not particularly limited. In some embodiments, the cross-sectional shape of the inorganic fibers is flat, and the ratio of the average major axis to the average minor axis of the flat shape (ratio = "major axis" ÷ "minor axis") is from 3 to 5. The reason for this is that the strength of the surface nonwoven fabric layer and the texture of the nonwoven fabric layer are well balanced. In some embodiments, the cross-sectional shape of the inorganic fiber is flat, and the equivalent fiber diameter of the flat shape is 5 μm or more and 17 μm or less. This is because it is advantageous in producing inorganic fibers. The equivalent fiber diameter means the diameter of the cross section of an inorganic fiber having a circular cross-sectional shape and having the same cross-sectional area as the cross-sectional area of ​​the inorganic fiber having a flat cross-sectional shape.

[0017] In some embodiments, the average fiber length of the inorganic fibers is in the range of 1 mm or more and 15 mm or less, because this provides a good balance between the strength of the surface nonwoven fabric layer and the texture of the surface nonwoven fabric layer.

[0018] In some embodiments, the backside nonwoven layer of the nonwoven laminate contains inorganic fibers, because this improves the heat resistance of the nonwoven laminate.

[0019] The inorganic fiber content in the substrate of the nonwoven fabric laminate is 70% by mass or more and less than 95% by mass relative to the substrate. If the inorganic fiber content in the substrate is less than 70% by mass, the heat resistance of the nonwoven fabric laminate cannot be obtained. On the other hand, if the inorganic fiber content in the substrate is 95% by mass or more, the strength of the nonwoven fabric laminate is deteriorated, and as a result, the shedding prevention effect of the inorganic fibers cannot be obtained.

[0020] The above-mentioned heat-adhesive binder fiber under moisture is a fiber that has a function of bonding inorganic fibers together in a surface nonwoven fabric layer. The heat-adhesive binder fiber under moisture is a fiber that flows or easily deforms from a fibrous state at a certain temperature in a wet state to exhibit a bonding function. The heat-adhesive binder fiber under moisture is a thermoplastic fiber that exhibits a bonding function in hot water or steam, for example, in the range of 80°C to 120°C. Examples of the heat-and-moisture adhesive binder fiber include polyvinyl fibers (polyvinylpyrrolidone, polyvinyl ether, polyvinyl alcohol, polyvinyl acetal, etc.), cellulosic fibers (C1-3 alkyl cellulose such as methyl cellulose, hydroxy C1-3 alkyl cellulose such as hydroxymethyl cellulose, carboxy C1-3 alkyl cellulose such as carboxymethyl cellulose, or salts thereof, etc.), and fibers made of modified vinyl copolymers (copolymers of vinyl monomers such as isobutylene, styrene, ethylene, or vinyl ether with unsaturated carboxylic acids such as maleic acid, or copolymers of anhydrides thereof, or copolymers of salts thereof). In some embodiments, the thermal adhesive binder fiber under moisture is one or more fibers selected from the group consisting of these.

[0021] In some embodiments, the heat-adhesive binder fiber under moisture is a polyvinyl fiber. In at least one embodiment, the heat-adhesive binder fiber under moisture is a polyvinyl alcohol (hereinafter, also referred to as "PVA") fiber. The reason for this is that the binder fiber has excellent film-forming ability in the surface nonwoven fabric layer, and as a result, the ability to inhibit the inorganic fibers from falling off from the surface nonwoven fabric layer can be improved. In some embodiments, the PVA fiber is a modified PVA fiber modified with a compound having a crosslinkable functional group, or a crosslinked PVA fiber crosslinked under mild conditions during or after spinning using a crosslinking agent. This is because the hot water resistance of the PVA fiber is improved. Examples of the crosslinkable functional group include a silanol group, a carboxyl group, and a methylol group.

[0022] The modified PVA fiber can be dissolved in water and spun without crosslinking the crosslinkable functional group by adjusting, for example, the pH. The modified PVA fiber can be crosslinked during or after spinning. In some embodiments, the degree of modification of the crosslinkable functional group is 0.01 mol% or more and 10 mol% or less. In some embodiments, the modified PVA fiber is a silanol-modified polyvinyl alcohol fiber. This is because the bond between the silanol-modified polyvinyl alcohol fiber and the inorganic fiber is improved, and as a result, the inorganic fiber can be prevented from falling off from the surface nonwoven fabric layer. The silanol-modified polyvinyl alcohol fiber can be obtained, for example, by dissolving silanol-modified polyvinyl alcohol (modification degree 0.1 mol% to 2 mol%) in an alkaline solution (pH 9 to 13), making the solution acidic (pH 5 to 6) to crosslink the fiber while spinning it, drying it, and then heat-treating it.

[0023] The crosslinked PVA fiber can be obtained by adding various inorganic or organic crosslinking agents to unmodified PVA without self-crosslinking property during or after spinning. Examples of the inorganic crosslinking agent include phosphoric acid, ammonium phosphate, ammonium sulfate, and titanyl sulfate. Examples of the organic crosslinking agent include methylol, epoxy, isocyanate, and aldehyde. The crosslinked PVA fiber can be obtained, for example, by adding a crosslinking agent to an unmodified PVA spinning dope and spinning it, or by spinning unmodified PVA alone and passing it through a bath containing a crosslinking agent, and then crosslinking the crosslinking agent by heat treatment. The crosslinked PVA fiber can also be obtained by using these methods in combination.

[0024] In some embodiments, the thermal adhesive binder fiber under moisture has a fineness of 0.1 dtex or more and 5.6 dtex or less, because the cost of the thermal adhesive binder fiber under moisture is advantageous and the ability to suppress the inorganic fibers from falling off from the surface nonwoven fabric layer can be improved. In some embodiments, the heat-adhesive binder fiber under moisture has a fiber length of 1 mm or more and 15 mm or less, because this is advantageous in preventing the heat-adhesive binder fiber under moisture from falling off the papermaking wire during papermaking and in improving the texture of the nonwoven fabric layer.

[0025] In some embodiments, the content of the heat adhesive binder fiber under moisture in the surface nonwoven fabric layer is from 1% by mass to 20% by mass relative to the surface nonwoven fabric layer, because this improves the heat resistance of the surface nonwoven fabric layer.

[0026] The fibrillated fibers are fibers obtained by physically grinding fibers such as cellulose using various beating machines or homogenizing devices such as a beater, a conical refiner, a single disc refiner, a double disc refiner, a stone mill grinder, a homogenizer, a high-pressure homogenizer, and a sand mill, so that the surfaces of the fibers before the grinding and the fibers themselves are very finely cracked and branched, and at least some of the branch ends have a fiber diameter of 1 μm or less. Examples of the fibrillated fibers include fibers obtained by fibrillating resins such as cellulose, solvent-spun cellulose, acrylic, wholly aromatic polyamide, wholly aromatic polyester, polyimide, polyamideimide, polyetheretherketone, polyethersulfone, polyphenylene sulfide, polybenzimidazole, poly-p-phenylenebenzobisthiazole, poly-p-phenylenebenzobisoxazole, and polytetrafluoroethylene. Examples of the wholly aromatic polyamides include para-aromatic polyamides such as poly(p-phenyleneisophthalamide) and poly(p-phenyleneterephthalamide), and meta-aromatic polyamides such as poly(m-phenyleneisophthalamide) and poly(m-phenyleneterephthalamide).

[0027] In some embodiments, the fibrillated fiber is a fibrillated cellulose fiber obtained by fibrillating cellulose fiber. This is because it can improve the suppression of inorganic fibers from falling off from the surface nonwoven fabric layer and is advantageous in terms of operability when the nonwoven fabric is manufactured by a papermaking method. Examples of the cellulose fiber include natural cellulose fiber and regenerated cellulose fiber. Examples of the natural cellulose fiber include wood pulp such as softwood pulp and hardwood pulp, and woody or herbaceous pulp such as straw pulp, bamboo pulp, linter pulp, and kenaf pulp. Examples of the regenerated cellulose fiber include rayon, cupra, and lyocell. Examples of the cellulose fiber include pulp obtained from waste paper and paper breakage generated in paper mills.

[0028] In some embodiments, the fibrillated fiber is a fiber obtained by fibrillating one or more materials selected from the group consisting of softwood pulp, linter pulp, and lyocell. In at least one embodiment, the fibrillated fiber is a fiber obtained by fibrillating lyocell. This is because it can improve the shedding suppression properties of inorganic fibers.

[0029] Examples of the apparatus for fibrillating fibers include beaters, conical refiners, single-disk refiners, double-disk refiners, PFI mills, stone-type grinders, homogenizers, and sand mills, as well as ball mills, dyno mills, mixers, grinders, rotary blade homogenizers that apply shearing force with high-speed rotary blades, double-cylinder high-speed homogenizers that generate shearing force between a cylindrical inner blade rotating at high speed and a fixed outer blade, ultrasonic crushers that pulverize fibers by ultrasonic impact, and high-pressure homogenizers that apply a pressure difference of at least 20 MPa to a fiber suspension, pass it through a small-diameter orifice at high speed, collide with it, and rapidly decelerate it to apply shearing force and cutting force to the fibers. One or more of the apparatuses for fibrillation can be used. The processing conditions of the apparatus can be appropriately set, for example, fiber concentration, temperature, pressure, rotation speed, shape of the refiner blades, gap between the refiner plates, and number of processing times.

[0030] The degree of fibrillation can be estimated by measuring the modified freeness of the fibrillated fiber. The smaller the value of the modified freeness, the more fibrillated the fiber. The modified freeness is a value determined in accordance with JIS P8121-2:2012 "Pulp - Freeness test method - Part 2: Canadian standard freeness method" except that an 80-mesh wire screen with a wire diameter of 0.14 mm and an opening of 0.18 mm is used as the sieve plate and the concentration of the sample is 0.1% by mass. In some embodiments, the modified freeness of the fibrillated fibers is 0 ml or more and 300 ml or less, because this improves the strength of the surface nonwoven fabric layer and improves the ability to prevent the inorganic fibers from falling off from the surface nonwoven fabric layer.

[0031] In some embodiments, the fibrillated fibers have a length-weighted average fiber length of 0.02 mm or more and 1.50 mm or less, because this can improve the ability to inhibit the inorganic fibers from falling off from the surface nonwoven fabric layer and improve the texture of the surface nonwoven fabric layer.

[0032] In some embodiments, the fibrillated fibers have an average fiber width of 0.5 μm or more and 40.0 μm or less, because this improves the strength of the nonwoven fabric layer and improves the ability to prevent the inorganic fibers from falling off from the surface nonwoven fabric layer.

[0033] The length-weighted average fiber length of fibrillated fibers was measured using a Fiber Quality Analyzer (FQA-360) manufactured by OpTest Equipment Inc. in accordance with JIS P8226-2:2011 "Pulp - Fiber length measurement method by optical automatic analysis method, Part 2: Non-polarized method." The average fiber width of the fibrillated fibers is the fiber width measured in projected fiber length (Proj) mode using Kajaani FiberLab V3.5 from Metso Automation.

[0034] In some embodiments, the content of fibrillated fibers in the surface nonwoven fabric layer is from 1% by mass to 20% by mass relative to the surface nonwoven fabric layer, because this improves the heat resistance and strength of the surface nonwoven fabric layer.

[0035] The heat-fusible binder fiber is a binder fiber that is softened by heating to exhibit an adhesive function. Examples of the heat-fusible binder fiber include composite fibers such as core-sheath fibers (core-shell type), parallel fibers (side-by-side type) and radially split fibers, undrawn fibers, and low-melting synthetic resin monofilaments. The heat-fusible binder fiber has a low glass transition temperature or melting temperature (melting point) in its entirety or in part, and exhibits an adhesive function in the drying process of a papermaking machine. In some embodiments, the heat-fusible binder fiber is the above-mentioned composite fiber. This is because composite fibers are difficult to form a film, and therefore the strength of the backside nonwoven fabric layer can be obtained while retaining the inherent interfiber voids of the nonwoven fabric, which are advantageous in terms of heat resistance. Examples of composite fibers include a combination of polypropylene (core) and polyethylene (sheath), a combination of polypropylene (core) and ethylene vinyl alcohol (sheath), a combination of high-melting point polyester (core) and low-melting point polyester (sheath), and a combination of high-melting point polyester (core) and polyethylene (sheath). The undrawn fibers may be, for example, undrawn fibers of polyester or the like. The low melting point synthetic resin short fibers may be, for example, monofilaments made only of a low melting point resin such as polyethylene or polypropylene.

[0036] In some embodiments, the content of the heat-fusible binder fiber in the back nonwoven fabric layer is 30% by mass or more relative to the back nonwoven fabric layer. This is because the adhesion between the front nonwoven fabric layer and the back nonwoven fabric layer is improved. As a result, the inorganic fibers passing through the back nonwoven fabric layer can be prevented from falling off. This is also because even if the back nonwoven fabric layer contains inorganic fibers to improve the heat resistance of the nonwoven fabric laminate, the heat-fusible binder is sufficiently present in the back nonwoven fabric layer to bond with the inorganic fibers, and the inorganic fibers can be prevented from falling off from the back nonwoven fabric layer. In at least one embodiment, the back surface nonwoven fabric layer has a thermally adhesive binder fiber content of 30 mass % or more relative to the back surface nonwoven fabric layer, and further contains inorganic fibers.

[0037] In addition to the inorganic fibers, the heat-adhesive binder fibers under moist conditions, and the fibrillated fibers, the surface nonwoven fabric layer may contain one or more of various other fibers conventionally known in the field of nonwoven fabrics, such as heat-fusible binder fibers, recycled fibers, and synthetic resin fibers, as well as various additives conventionally known in the field of nonwoven fabrics, such as fillers and defoamers, within the range that does not impair the effects of the present invention and as necessary. In addition to the heat-fusible binder fibers and inorganic fibers, the back nonwoven fabric layer may contain one or more of various other fibers conventionally known in the field of nonwoven fabrics, such as moist heat-adhesive binder fibers, fibrillated fibers, regenerated fibers, and synthetic resin fibers, as well as various additives conventionally known in the field of nonwoven fabrics, such as fillers and defoamers, within the range that does not impair the effects of the present invention and as necessary.

[0038] In some embodiments, the substrate has a total thickness of 0.1 mm to 0.8 mm including the front nonwoven fabric layer and the back nonwoven fabric layer, because this improves the strength of the substrate, improves operational stability during production of the substrate, and is advantageous in terms of production costs.

[0039] In some embodiments, the substrate has a total density of 0.10 g / cm 3 including the front nonwoven fabric layer and the back nonwoven fabric layer. 3 More than 0.50g / cm 3 The reason for this is that the strength of the substrate and the operational stability during the production of the substrate are improved.

[0040] The substrate having a two-layer structure of a front nonwoven fabric layer and a back nonwoven fabric layer can be obtained by a method conventionally known in the field of nonwoven fabrics, such as a combination papermaking machine having a cylindrical, fourdrinier, short wire, or inclined wire screen and combining the same or different types of screens from the screens, or a papermaking machine having multiple head boxes and overlapping wet paper on a wire. In addition to the above-mentioned fibers, dispersants, paper strength agents, thickeners, inorganic fillers, organic fillers, antifoaming agents, etc. may be added to the raw material slurry as required.

[0041] In some embodiments, the concentration of the raw material slurry containing each fiber is 0.001% by mass or more and 0.5% by mass or less. In at least one embodiment, the raw material slurry is further diluted to a predetermined concentration to form a papermaking slurry, which is then paper-made to form a wet web. The obtained wet paper web is nipped with a press roll or the like, and then dried using a Yankee dryer to become a substrate. At this time, the moist heat adhesive binder fiber of the surface nonwoven fabric layer exhibits a binding function due to the heat of drying, and the substrate can have strength. The substrate is dried using a Yankee dryer, so that the substrate surface becomes flat and has a surface with few irregularities. In addition, a heating device such as a hot air dryer, a heating roll, or an infrared heater can be used in combination with the Yankee dryer as an auxiliary drying method. In some embodiments, the drying temperature is such that the moisture of the wet paper web can be sufficiently removed and the moist heat adhesive binder fiber can exhibit the binding function.

[0042] The inorganic particle layer is a layer containing inorganic particles. In some embodiments, the inorganic particle layer is a layer containing inorganic particles and a binder, because this makes it easier to form the inorganic particle layer. The nonwoven fabric laminate has the inorganic particle layer on both sides of the substrate. The inorganic particle layer covers both sides of the substrate and penetrates into voids in the substrate, so that the nonwoven fabric laminate can obtain heat resistance. Furthermore, the inorganic particle layer covers the substrate, so that the nonwoven fabric laminate can improve the ability to suppress the shedding of inorganic fibers.

[0043] The inorganic particles are conventionally known. In some embodiments, the inorganic particles have good water dispersibility. This is because it is advantageous when providing an inorganic particle layer on both sides of a substrate. Examples of inorganic particles include aluminum hydroxide, aluminum hydroxide oxide, magnesium hydroxide, calcium hydroxide, dihydrated gypsum, tricalcium aluminate, clay, kaolin, calcined kaolin, carbonates such as calcium carbonate, magnesium carbonate, and barium carbonate, talc, and titanium dioxide. In some embodiments, the inorganic particles are one or more selected from the group consisting of the above. In at least one embodiment, the inorganic particles are one or more selected from the group consisting of aluminum oxide hydroxide, clay, kaolin, calcined kaolin, and carbonates, because this improves the heat resistance and strength of the nonwoven fabric laminate.

[0044] In some embodiments, the average particle size of inorganic particles is 0.08 μm or more and 20.0 μm or less. This is because the heat resistance of the nonwoven fabric laminate is improved. Here, the average particle size of inorganic particles refers to the D50 value obtained from the volume-based particle size distribution obtained by diluting inorganic particles with water to a predetermined concentration, dispersing the inorganic particles with a stirrer, and measuring the obtained inorganic particle dispersion with a laser scattering type particle size measuring instrument, for example, Microtrac's product name: MT3000.

[0045] The binder is one or more selected from the group consisting of conventionally known organic binders and inorganic binders. In some embodiments, from the viewpoint of stably forming the inorganic particle layer, the binder of the inorganic particle layer is one or more selected from the group consisting of organic binders. In some embodiments, from the viewpoint of forming the inorganic particle layer, the binder of the inorganic particle layer is one or more selected from the group consisting of inorganic binders.

[0046] Examples of the organic binder include, in addition to the resins exemplified above for the moist heat adhesive binder fiber, fibrillated fiber, and heat fusible binder fiber, styrene-butadiene-based, styrene-acrylonitrile-based, ethylene-acrylonitrile-based, vinyl chloride-vinyl acetate-based, and ethylene-vinyl acetate-based copolymer resins, urethane-based resins, alkyd-based resins, and polyester-based resins, as well as thermosetting synthetic resins such as melamine resins and urea resins, natural rubbers, starches, polypropylene glycol, and polyethylene glycol.

[0047] Examples of the inorganic binder include inorganic types of inorganic binders such as sepiolite, colloidal silica, water glass, alumina sol, and bentonite.

[0048] The method of providing the inorganic particle layer on the substrate can be a method of coating the substrate with a coating liquid for the inorganic particle layer. For example, the coating can be a method using a coating device conventionally known in the coating field. For example, the coating device can be a two-roll size press, a gate roll coater, a gravure coater, a die coater, a lip coater, a blade coater, a curtain coater, an air knife coater, a rod coater, a kiss coater, a dip coater, and the like.

[0049] The medium for preparing the coating liquid for the inorganic particle layer is, for example, one in which the inorganic particles and binder, as well as other additives used as necessary, can be uniformly dissolved and / or dispersed. Examples of the medium include organic media such as aromatic hydrocarbons such as toluene, ethers such as tetrahydrofuran, ketones such as methyl ethyl ketone, alcohols such as isopropyl alcohol, N-methyl-2-pyrrolidone (NMP), dimethylacetamide, dimethylformamide, and dimethylsulfoxide, and aqueous media such as ion-exchanged water, distilled water, and pure water. In some embodiments, the medium is one or more selected from the group consisting of the organic and aqueous systems. In some embodiments, the solvent does not swell or dissolve the substrate. In at least one embodiment, the medium for preparing the coating liquid for the inorganic particle layer is water.

[0050] In some embodiments, the nonwoven fabric laminate has an inorganic particle layer content of 16% by mass or more and 66% by mass or less relative to the mass of the nonwoven fabric laminate. Here, the inorganic particle layer content is the total value of the inorganic particle layers present on both sides of the substrate of the nonwoven fabric laminate. The content is determined by the basis weight (g / m2) of the nonwoven fabric laminate and the substrate. 2 ) and the coating weight of the inorganic particle layer (g / m 2 ) can be calculated from the coating amount (g / m2) of the inorganic particle layer on both sides of the substrate. 2 ) is the basis weight (g / m2) of the nonwoven fabric laminate 2 ) to the basis weight (g / m 2) can be calculated by subtracting the basis weight (g / m 2 ) is a value determined in accordance with JIS P8124:2011 "Paper and paperboard -- Method of measurement of basis weight." In some embodiments, in the nonwoven fabric laminate, the mass ratio (dry solid content) of the inorganic particle layer relative to the surface nonwoven fabric layer of the substrate and the inorganic particle layer relative to the back nonwoven fabric layer of the substrate (inorganic particle layer relative to the surface nonwoven fabric layer:inorganic particle layer relative to the back nonwoven fabric layer) is in the range of 7:3 to 3:7. The reason for this is that the heat resistance, strength, and flexibility of the nonwoven fabric laminate are improved in harmony.

[0051] Other additives used as necessary in the coating liquid for the inorganic particle layer include, in addition to the inorganic particles and the binder, various conventionally known additives such as dispersants, thickeners, water retention agents, wetting agents, preservatives, and antifoaming agents. EXAMPLES

[0052] The present invention will be described below with reference to examples. However, the present invention is not limited to these examples. In the examples, the units "mass% (mass percentage)" and "parts by mass" refer to the value of the dry solid content and / or the substantial component unless otherwise specified. In addition, the coating amount (g / m 2 ) means the mass of dry solids per square meter.

[0053] <Base material> A raw material slurry for the surface nonwoven fabric layer containing inorganic fibers, moist heat adhesive binder fibers and / or fibrillated fibers was prepared using a vertical pulper. The raw material slurry was made into a wet paper for the surface nonwoven fabric layer by a wet papermaking method using an inclined wire system. A raw material slurry for the back nonwoven fabric layer containing inorganic fibers and / or heat fusible binder fibers was prepared using a vertical pulper. The raw material slurry was made into a wet paper for the back nonwoven fabric layer using a cylinder papermaking machine, which was then laminated on the wet paper for the surface nonwoven fabric layer. The wet paper was then dried using a Yankee dryer at a surface temperature of 130°C so that the inclined wire surface was in contact with the Yankee dryer to obtain a substrate. The basis weights (g / m2) of the surface nonwoven fabric layer and the back nonwoven fabric layer were calculated using the following formula: 2The papermaking conditions were adjusted so that the specified values ​​were obtained. The basis weights are shown in Tables 1 and 2. The papermaking speed was 20 m / min. In Comparative Example 6, the substrate was one in which the back nonwoven fabric layer was not laminated to the front nonwoven fabric layer.

[0054] [Table 1]

[0055] [Table 2]

[0056] The following fibers were used for each of the fibers listed in Tables 1 and 2.

[0057] Inorganic fiber 1: Glass fiber with a flat cross section. Manufactured by Nitto Boseki Co., Ltd. Average long diameter: 28 μm, average short diameter: 7 μm, average fiber length: 13 mm. Inorganic fiber 2: Glass fiber with circular cross section. Manufactured by Nitto Boseki Co., Ltd., average fiber diameter 10.5 μm, average fiber length 6 mm. Moisture-heat adhesive binder fiber: silanol-modified PVA fiber. Manufactured by Kuraray Co., Ltd., product name: SPG (registered trademark) 056-11, fineness 0.6 decitex, fiber length 3 mm. Fibrillated fiber 1: A fibrillated fiber made from cellulose from lyocell fibers. Fibrillated fiber 2: A fibrillated fiber made of meta-aromatic polyamide. Heat-bondable binder fiber: Sheath-core binder fiber. Teijin, product name TJ04CN, Fineness: 1.1 decitex, fiber length: 5 mm.

[0058] <Fibrillated fiber 1> Fibrillated fiber 1 was a fibrillated fiber made of cellulose with a length-weighted average fiber length of 0.8 mm, an average fiber width of 8 μm, and a modified freeness of 90, which was prepared by processing Lyocell fiber (fineness 1.7 dtex, length-weighted average fiber length 3 mm) using a double disc refiner to adjust the amount of branches produced from the trunk.

[0059] <Fibrillated fiber 2> Fibrillated fiber 2 was prepared by dissolving 10 parts by mass of poly(m-phenylene isophthalamide) having a logarithmic viscosity of 1.5 in sulfuric acid in 90 parts by mass of N,N-dimethylacetamide containing 15 parts by mass of lithium chloride, introducing the resulting solution into an aqueous glycerin solution in a homomixer rotating at high speed to produce a pulp-like material, and processing the pulp-like material using a double disc refiner to produce fibrillated fiber made of meta-aromatic polyamide.

[0060] <Coating fluid for inorganic particle layer> 90 parts by mass of kaolin (manufactured by BASF CORPORATION, product name: ASP (registered trademark) NC X-1), 9.5 parts by mass of polyvinyl alcohol (manufactured by Japan Vinyl Acetate & Poval, product name: VC-13) as a binder, and 0.5 parts by mass of a water-soluble acrylic acid-based dispersant (manufactured by Toagosei Co., Ltd., product name: Aron (registered trademark) T-50) were mixed in water and thoroughly stirred, and the concentration was adjusted with water to prepare a coating liquid for the inorganic particle layer with a solids concentration of 50% by mass.

[0061] <Coating of inorganic particle layer> The following coating device was used to apply the coating liquid for the inorganic particle layer to the substrate. Method 1: Roll size press Method 2: Kiss coater

[0062] Tables 1 and 2 show the parts by mass of each fiber contained in each nonwoven fabric layer by blending each fiber in the raw material slurry of the nonwoven fabric layer.

[0063] <Nonwoven fabric laminate (method 1)> The substrate was impregnated with the coating liquid for the inorganic particle layer and coated on both sides thereof, and the gap between the rolls was controlled using a two-roll size press having a gap adjustment function (cotter) to adjust the wet coating amount, and the substrate was dried to obtain a nonwoven fabric laminate. Here, the mass ratio (ratio of dry solid mass) of the inorganic particle layer relative to the surface nonwoven fabric layer of the substrate to the inorganic particle layer relative to the back nonwoven fabric layer of the substrate was "inorganic particle layer relative to surface nonwoven fabric layer":"inorganic particle layer relative to back nonwoven fabric layer" = 1:1.

[0064] <Nonwoven fabric laminate (method 2)> The inorganic particle layer coating liquid was applied to both sides of the substrate using a kiss coater, the concentration of the inorganic particle layer coating liquid was controlled to adjust the coating amount, and the substrate was dried to obtain a nonwoven fabric laminate. Here, the mass ratio (ratio of dry solid mass) of the inorganic particle layer relative to the surface nonwoven fabric layer of the substrate to the inorganic particle layer relative to the back nonwoven fabric layer of the substrate was "inorganic particle layer relative to surface nonwoven fabric layer":"inorganic particle layer relative to back nonwoven fabric layer" = 1:1.

[0065] The substrates and nonwoven fabric laminates of each Example and Comparative Example were evaluated as follows. The evaluation results are shown in Tables 1 and 2. Here, the "front surface" and "back surface" in Tables 1 and 2 refer to the "front surface nonwoven fabric layer" and the "back surface nonwoven fabric layer," respectively.

[0066] Tables 1 and 2 show the "content of inorganic fiber relative to the substrate (% by mass)" in the substrate, the "content of heat-adhesive binder fiber relative to the surface nonwoven fabric layer (% by mass)" in the surface nonwoven fabric layer, the "content of fibrillated fiber relative to the surface nonwoven fabric layer (% by mass)" in the surface nonwoven fabric layer, the "content of heat-fusible binder fiber relative to the surface nonwoven fabric layer (% by mass)" in the back nonwoven fabric layer, and the "basis weight (g / m 2) and "Amount of inorganic particle layer applied on both sides of substrate (g / m 2 ) and "Coating method for inorganic fine particle layer."

[0067] <Basis weight and coating amount> It was determined in accordance with JIS P8124:2011 "Paper and paperboard - Measurement method for basis weight." The coating weight of the inorganic particle layer was calculated by subtracting the basis weight of the substrate from the basis weight of the nonwoven fabric laminate.

[0068] <Falling of inorganic fibers> A test piece measuring 50 mm in width direction × 200 mm in machine direction was cut out of the nonwoven fabric laminate, and the front and back sides were rubbed 5 times each with a black cloth, and the loss of inorganic fibers was visually observed. From the observation results, the loss of inorganic fibers on the front and back sides of the nonwoven fabric laminate was evaluated according to the following criteria. A: The number of inorganic fibers that fell off was in the range of 5 or less. B: The number of fallen inorganic fibers was in the range of 6 to 20. C: The number of inorganic fibers that fell off was in the range of more than 20 fibers.

[0069] The heat resistance of the nonwoven fabric laminate was evaluated from the standpoint of fire resistance and non-combustibility.

[0070] <Heat resistance (fire resistance)> Three pieces of the nonwoven fabric laminate with a size of 100 mm in the width direction × 100 mm in the machine direction were cut out as test pieces, and a flame from a burner (product name: Laboburner APTL, manufactured by Phoenixdent) was applied to the center of each test piece for 5 minutes on the side having the surface nonwoven fabric layer of the nonwoven fabric laminate. Thereafter, the surface of the nonwoven fabric laminate on the side where the flame was applied was visually observed. From the observation results, the fire resistance was evaluated according to the following criteria. The flame temperature of the burner was 1000°C. A: No holes, cracks or deterioration are found on the surface. B: There are no holes, cracks or melting on the surface, but Slight deterioration such as melting marks or dents is observed. C: There are holes or cracks on the surface.

[0071] <Heat resistance (nonflammable)> Two test pieces measuring 100 mm in width direction × 100 mm in machine direction were cut out from the nonwoven fabric laminate, and each test piece was inserted with the surface nonwoven fabric layer of the nonwoven fabric laminate facing upwards in an electric furnace capable of maintaining a temperature of 750°C ± 5°C, and the condition of the test piece was visually observed. The observation results were evaluated according to the following criteria. A: It does not ignite after insertion. B: After insertion, it ignites for a moment. C: After insertion, it ignites, not instantly like B above.

[0072] The results in Tables 1 and 2 show that the nonwoven fabric laminates of each example that satisfy the configuration of the present invention have dimensional stability and are less likely to produce fluff, while also inhibiting the shedding of inorganic fibers and providing high heat resistance. Although the evaluation is not shown in Table 2, in Example 19, from the viewpoint of the balance of heat resistance, strength and flexibility of the nonwoven fabric laminate, some deterioration in flexibility is observed. On the other hand, it is clear that the nonwoven fabric laminates of the comparative examples, which do not satisfy the constitution of the present invention, are unable to combine the ability to inhibit the inorganic fibers from falling off with high heat resistance.

[0073] Mainly from a comparison between Example 1 and Example 4, it is apparent that when the back surface nonwoven fabric layer contains inorganic fibers, the heat resistance of the nonwoven fabric laminate is improved.

[0074] Mainly from a comparison between Examples 1 to 3, it can be seen that when the cross-sectional shape of the inorganic fibers in the surface nonwoven fabric layer is flat, or when the fibrillated fibers are fibers obtained by fibrillating lyocell fibers, the ability to suppress shedding of the inorganic fibers is improved.

[0075] Mainly from a comparison between Comparative Example 4 and Examples 10 to 12, it is clear that the heat resistance is improved when the content of the heat adhesive binder fiber under moisture in the surface nonwoven fabric layer is 1% by mass or more and 20% by mass or less with respect to the surface nonwoven fabric layer.

[0076] Mainly from a comparison between Comparative Example 5 and Examples 13 to 15, it can be seen that when the content of fibrillated fibers in the surface nonwoven fabric layer is 1% by mass or more and 20% by mass or less with respect to the surface nonwoven fabric layer, the heat resistance and strength of the surface nonwoven fabric layer are improved, and as a result, the ability to suppress shedding of inorganic fibers is improved. [Industrial Applicability]

[0077] The nonwoven fabric laminate of the present invention can be used for nonwoven fabrics that require heat resistance in the fields of building materials, automobile parts, and industrial materials, and can be suitably used for nonwoven fabrics that are to be processed into heat-resistant members.

Claims

1. A nonwoven fabric laminate comprising a substrate and inorganic particle layers on both sides of the substrate, the substrate having a two-layer structure including a nonwoven fabric layer containing inorganic fibers, a heat-adhesive binder fiber under moist conditions, and a fibrillated fiber, and a nonwoven fabric layer containing heat-fusible binder fibers, the content of the inorganic fibers in the substrate being 70% by mass or more and less than 95% by mass with respect to the substrate, and the inorganic particle layer containing inorganic particles.

2. The nonwoven fabric laminate of claim 1 , wherein the inorganic particle layer comprises a binder.

Citation Information

Patent Citations

  • Nonwoven fabric made of wet method and method for producing the same

    JP2015086477A

  • Fireproof sheet for backing wallpaper

    JP2022001677A

  • Fireproof sheet for wallpaper backing

    JP2023043470A

  • Fire-resistant sheet for wall paper lining

    JP2023078680A